A case report of prostate cancer presenting as a symptomatic pelvic mass mimicking lymphoma. (2020) - Mahjoubi, Zied; Bibi, Mokhtar; Hedhli, Houssem; Ouanes, Yassine; Rhouma, Sami Ben; Yassine, Nouira
Highlights: Metastatic prostate cancer presenting as a large pelvic mass mimicking lymphoma. CT scan confirmed a large lobulated necrotic pelvic and extraperitoneal mass. Bilateral orchidectomy was performed. The main treatment for metastatic prostate cancer is hormone therapy. External beam radiotherapy is proven to help decreasing tumor volume. Abstract: Introduction: Metastatic prostate cancer is a relatively common condition in elderly men. The aim of this paper is to report a rare case of metastatic prostate cancer presenting as a large pelvic mass mimicking lymphoma and to discuss its management. Presentation of Case: An 85-year-old patient was complaining of lower urinary tract symptoms, and significant pelvic swelling. On physical examination, a 15-cm pelvic mass and lumpy prostate were found. Laboratory investigations revealed elevated PSA levels (PSA=300g/mL). CT scan showed a large lobulated necrotic pelvic mass and multiple swollen lymphnodes. The diagnosis of an atypical pelvic lymphoma associated with a metastatic prostate cancer was first evoked. An ultrasonography-guided biopsy of the mass was carried. The immunohistochemical study confirmed prostate adenocarcinoma. A bilateral orchiectomy was performed. A follow up of 3 months showed a decrease of PSA without shrinkage of the mass. Discussion: A metastatic prostate cancer presenting as a compressive pelvic mass mimicking other diagnosis such as lymphomas, is a rare circumstance of discovery. In our case, atypical pelvic lymphoma was evoked based on the association of multiple retroperitoneal enlarged lymphnodes. Histological findings of the biopsy rectified the diagnosis and confirmed prostate adenocarcinoma. The main treatment for such metastatic prostate cancers remains hormone therapy. Some authors reported external beam radiotherapy in order to reduce prostate volume. Conclusion: Prostate cancer should be considered in the assessment of large pelvic masses. Digital rectal examination and testing PSA levels can lead to the diagnosis. After histological confirmation, the androgen deprivation is the main treatment.